Geboren als ein Beschnittener: eine Betrachtung zum Konzept der Vollkommenheit im historischen Kontext einiger jüdischer Quellen - Kalimi, Isaac (Biblische Notizen, 2004)
According to the rabbinical concept to be born circumcised means to be without blemish. It is considered an initial sign of a forthcoming important personality. The roots of the idea can be found in the book of Jubilees, in a passage related to Antiochus IV Epiphanes who outlawed circumcision. Later on, in Liber Antiquitatum Biblicarum, Pseudo-Philo describes Moses as one who was born circumcised. The idea can be traced, possibly, also to the Fourth Gospel, which makes an analogy between a sick man and an uncircumcised man. It was developed the most, however, in Midrashim which listed several renowned biblical figures, and claimed that they were born circumcised. One can better appreciate these homilies specifically against the historical background of the events in the Land of Israel in the second half of the first and the first half of the second centuries CE, that is, the dispute with the Pauline Christianity concerning circumcision and the Hadrianic ban of circumcision.